An Analysis of The Ability to Design A Handmade Batik The Work of Students SMKN 14 Bandung - Andini, Dinda Sri; Abas, Tati; Ningsih, Mirna Purnama (Prodi PKK - Departemen PKK - Universitas Pendidikan Indonesia, 2018)
Research discuss problems of the ability school tuition in designing a batik wrote program kriya textile in SMKN 14 Bandung. This research discuss analysis the ability to design a batik wrote as one of competence that must be they have been given. The purpose of this research an analysis the ability in designing a batik wrote as the work students covering, The students in positioning the main motivation for handmade batik, Primary school students in ability in completing design with a batik appendages, The ability school tuition in applying a kind of isen against the main motivation for and motives appendages, The ability school tuition in designing motive by taking into account element neatness, beauty, and creativity in design a batik wrote, This research uses the method descriptive, with a data collection of guidelines review of sheets of the work of design school tuition as many as 15 respondents. The research results obtained that: (1) The ability school tuition in designing a batik wrote each, most of them are have the ability the main motivation as an ornament central in the plane of pillowcases, the ability motive appendages by doing repetition the main motivation as penyempurna design a batik as a whole. And most again capability in in applying a kind of isen the line and ukel as filler for the field of the main motivation for and motives appendages as features/characteristic of a batik. (2) The ability in designing a batik wrote students are able to apply elements neatness, the beauty of, creativity that looked at the appearance of a whole motive which he made before the handmade batik, though still a small number of students to apply design motive appendages by not using repetition of the main motivation for, while less than half that is capable of in applying neatness design elements with scratches the visible clearer, and more than half of whom not capable of taking into account the striations of design wrong and former an eraser that it is evident that there not clean/dirty to the field of design pillowcases.